The Effect of Pop-Up Book on Language Boarding House Students’ Vocabulary Mastery - Aisyah, Zilmi Kawila; Asri, Annisa Kurnia; Musdalifah (Teaching English as Foreign Language, Literature and Linguisticss, 2025)
Since vocabulary has the important role when learning English, it is better for the English learners to have sufficient vocabulary before learning the four English skills. However, the students’ vocabulary tends to be low because of the less interesting media for learning. Therefore, the present study aimed to find out the effect of pop-up book on students’ vocabulary mastery at Language Boarding House. Students must grasp their vocabulary in order to learn the entire language. Put another way, children find it easier to communicate when they have a larger vocabulary. The pre-experimental one group pre-test and post-test were created by the researcher using a quantitative approach. Twenty-six intermediate-level students made up the study's sample. To gather data, the researcher employed pre- and post-tests. The results of the study demonstrated that using pop-up books significantly improved pupils' vocabulary mastery. The paired sample t-test calculation result indicated that the sig. (2-tailed) value was less than 0.05. It indicates that pupils' vocabulary mastery is improved by pop-up books.